A numerical study on the responses of coastal water quality to river runoff after heavy rainfall in the case of a complex coastline with two artificial islands - Wang, Gang; Feng, Xin; Zhang, Jiabo; Huang, Zhe; Bai, Yuchuan; Song, Wei; Xu, Haijue (Frontiers in Marine Science, 2023)
Heavy rainfall causes large volume of freshwater and nutrient salts from rivers into the sea. It leads to great changes in the ecological environment of estuary waters in a short period of time. The responses of the estuarine hydro-environment become more complex with the concentrated construction of artificial structures which is one of the important reasons for the marine ecological disasters. This paper takes the Tang Estuary in Qinhuangdao as the prototype, where artificial structures (ports, artificial islands, bridge ) are concentrated, under the weak tidal dynamic environment. A nested model on hydrodynamics and water quality is established using delft3D model, with coupled waves and flows. The model is to simulate the spatial and temporal characteristics of the short-term responses of ecological environmental factors such as DIN、NO3-N、NH4-N、PO4-P under a heavy rainfall in August 2022. The results show that DIN and NO3-N still have high concentration in source areas after the flooding process. The concentration recovery to normal values about 5.5 days after the flooding process. While NH4-N and PO4-P show a response with temporal correspondence with the flooding process, and the concentration recovery takes only about 1 day. This paper proposes two short-term response modes of pollutant diffusions, which provide helps to explore the role of hydro-environment changes on offshore algal hazards and the effect of permeable buildings on pollutant dispersion. They further provide possibilities for the forecasting of red tide and green tide and the prevention in the future.